Screening of potential probiotics with anti-Helicobacter pylori activity from infant feces through principal component analysis. (August 2021) - Gao, Fei; Sui, Lin; Mu, Guangqing; Qian, Fang; Zhu, Xuemei
Abstract: Helicobacter pylori is considered as the causative agent of gastrointestinal diseases. The large increase of drug-resistant strains caused by the treatment of H. pylori makes it very important to develop new treatment strategies. This study aimed to isolate and select Lactobacillus strains from infant feces and evaluate the inhibitory effects against H. pylori . Six strains were initially screened out of Forty-seven Lactobacillus strains obtained from healthy infants feces through evaluating acid (pH 3.0) and bile salt tolerance (0.3%). Based on the re-screening of the four indexes of transit tolerance, hydrophobicity, self-aggregation and anti- Helicobacter pylori, combined with the comprehensive evaluation of principal component analysis, these both strains of IF-3083 and IF-5014 were obtained. And these two strains were identified as Lactobacillus plantarum using 16S ribosomal RNA gene sequences. Also, the two identified strains showed good adhesion to human gastric adenocarcinoma (AGS) and human colorectal adenocarcinoma (HT-29) cells, γ-hemolytic activity and susceptibility to seven antibiotics. The viable count of H. pylori SS1 was significantly decreased when co-cultured with the live cells (LC) or cell-free supernatants (CFS) of these two strains. These preliminary results suggested that L. plantarum IF-3083 and L. plantarum IF-5014 had the potential to be used as probiotics to prevent H. pylori infection.